Quo vadis, Tommotian?. (8th November 2019) - Grazhdankin, Dmitriy V.; Marusin, Vasiliy V.; Izokh, Olga P.; Karlova, Galina A.; Kochnev, Boris B.; Markov, Georgiy E.; Nagovitsin, Konstantin E.; Sarsembaev, Zhiger; Peek, Sara; Cui, Huan; Kaufman, Alan J.
Abstract: The concept of the Tommotian Regional Stage of the Siberian Platform has been closely linked to the idea of the 'Cambrian Explosion' of animals and protists when the entire Earth system shifted rapidly into Phanerozoic mode. We conducted a multidisciplinary study of an informal 'synstratotype' of the lower Tommotian boundary in the upper Mattaia Formation, Kessyusa Group in the Olenek Uplift, NE of the Siberian Platform. The Mattaia Formation characterizes an upper shoreface to inner-shelf depositional setting and provides important faunal ties and correlation with carbonate-dominated and aliminosiliciclastic open-shelf areas. A section of the upper Mattaia Formation at Boroulakh, Olenek River is suggested here as a model for the Global Boundary Stratotype Section and Point for the base of the Cambrian Stage 2. This level contains the lowermost occurrence of the cosmopolitan fossil helcionelloid mollusc Aldanella attleborensis . Section global markers near the base of the stage include a positive excursion of δ 13 C values reaching +5.4‰, a U–Pb zircon date of 529.7 ± 0.3 Ma, massive appearance of diverse small skeletal fossils (including Watsonella crosbyi ), a sudden increase in diversity and abundance of trace fossils, as well as a conspicuous increase in depth and intensity of bioturbation. Coincidently, it is this level that has always been regarded as the lower Tommotian boundary on the Olenek Uplift.